Becoming-Dinosaur: Towards a Morphology of Creative Involution (Altre Modernità, 2021)
Palaeontologist Jack Horner, along with molecular biologists and other experts, has been working on building an animal that he calls “the Chickenosaurus.” Horner’s purpose is to reverse-evolve a bird into a non-avian theropod by intervening on the genome expression of a chick’s embryo in ways that stimulate the formation of ancestral characteristics (activation of atavism). After a discussion of the project in its scientific detail, I offer a theoretical perspective on the topic that relies on concepts developed by Gilles Deleuze. In particular, I argue that the Chickenosaurus can be regarded as an eligible example of Deleuzian “becoming” and that it deserves philosophical attention in that it displays the “creative involution” through which novelty is produced.
Keywords: Gilles Deleuze; Jack Horner; palaeontology; Chickenosaurus; Body without Organs; egg